Effect of fructo-oligosaccharides on growth performance and meat quality in broilers - Yan, ZhiHui; Tang, XiaoWu; Wu, RunTao; Yang, Can; Jiang, YunMiao; Wang, Xuan; Tang, QingHai; Hu, YongLing; Wang, LeLi; Jiang, Zhi (Frontiers in Veterinary Science, 2025)
This study investigated the fructo-oligosaccharides (FOS) on growth performance and meat quality in broilers. Total 160 Xianghuang broilers aged 2 months were randomly assigned into 2 groups, CON (control), FOS (supplemented 0.5% fructo-oligosaccharides in diet). After 38 days, the breast, thigh muscle and liver samples were collected for further analysis. Results showed that no significant effect of 0.5% FOS on growth performance such as average daily gain (ADG), average daily feed intake (ADFI) or feed-to-gain ratio (F:G) were observed (P > 0.05). Broilers in FOS group had a yellower breast than that in CON group (P < 0.05). Breast pH45min and thigh pH24h value of FOS group were greater than that in CON group (P < 0.05). Max shear force and work of shear of cooked breast (pectoralis major) muscle was lower in FOS group compared with CON group (P < 0.05). Hardness (P = 0.065), fracturability (P = 0.063), gumminess (P = 0.079), chewiness (P = 0.080) of cooked thigh meat tended to be higher in FOS group compared to the CON group. Addition of 0.5% FOS resulted in lower thigh total superoxide dismutase (T-SOD) activity compared to CON group (P < 0.05). The malonaldehyde (MDA) concentration (P = 0.066) of breast muscle tended to be lower in FOS group compared with CON group. There was an increasing trend for total antioxidant capacity (T-AOC) activity of thigh muscle in FOS group compared to CON group (P = 0.053). Relative mRNA expression of breast catalase (CAT), superoxide dismutase 1 (SOD1), thioredoxin reductase 1 (TXNRD) were up-regulated by FOS supplementation compared with CON group (P < 0.05). In conclusion, FOS can be utilized at 0.5 % to improve meat quality such as elevating pH value, yellowness and decreasing max shear force of muscle through enhancing the antioxidant activity in broilers.